Improving Eight Grader Students’ Vocabulary By Using Love Song - Buntara Adi Purwanto; Arina Noviyani (Tinta Emas Publisher, 2024)
The lack of students’ vocabulary mastery had become the main factor of student’s difficulty in learning English. Overcoming the condition, the learning media along with it’s methodology need to be improved. In this research, researcher use the love song as the media in improving students’ vocabulary. The purpose of this study was to find out the improvement in increasing vocabulary mastery by using song as the media. This is a Classroom Action Research which was conducted in two cycles. There were three main instruments used in in this research, they are interview, observation and test. The result showed that there was improvement among the instruments. The interview showed that student’s mood in learning process was improved, the observation indicated an improvement from 68.3 in cycle I and 91.6 in cycle II. The test score was improved from 67.2 in pre-cycle to 73.4 in cycle and 81.7 in cycle 2.